Studying the effect of alcoholic extract of seeds, leaves and roots of Raphanus sativus radish (Journal of the College of Basic Education, 2022)
This study dealswith the crude alcoholic extract of( seeds, leaf and roots) of radish plant(Raphanus sativus) we prapared three different concentrations for all extracts (50%, 25%, 12.5% v/v ). The study detected antimicrobiol activity by using well diffuion in agar technique gianstall of bacteria :Staphylococcus aureus ,Pseudomonas aeruginosa, Escherchia coli , Proteus vulgaris ,Enterococcus Faecalis , Streptococcus pyogeness ,Bacillus thuringensis ,Klebsilla pneumonia. The study showed highest antibacterial activity of seeds of radish that attained highest persent of inhibition (33 mm) aginest P. vulgaris when using (50%) conc.,While attained lowest persent of inhibition (11mm) aginest P. aeuroginosa when using (12.5%)conc.Then leaf extract of radish that attained highest percent of inhibition (27mm) aginest E. coli and E. feacalis when using (50%)conc., while attained lowest percent activity aginst S. Pyogenes when using (12.5%)conc.This study revealed that the extract of roots of radish was in the last rank,that attained highest inhibition percent(25mm)aginest S. aureus in (50%) conc. ,and the lowest inhibition percent (10mm) aginest P. aeuroginosa in (12.5%)conc. ,And the root extract doesnot exhibited inhibition activity aginest E.coli ,E.Faecalis, S.pyogenes ,B.thurengensis